The Effect of Thermostat Condition on Thermal Stability and Combustion Emission Efficiency in an Inline 4-Cylinder Gasoline Engine - Agus Dwi Putra; Rangga Ega Santoso; Yayi Febdia Pradani; Diama Rizky Septiawan; Faqih Fadillah; Nicko Nur Rakhmaddian (Universitas Islam Malang, 2026)
This study investigates the effect of thermostat conditions on thermal stability and exhaust emission efficiency in a 1,300 cc inline 4-cylinder gasoline engine. The novelty of this research lies in the integrated evaluation of thermostat removal and thermostat failure on both engine temperature stability and combustion emissions under identical operating conditions. A quantitative experimental method was applied using three thermostat conditions: normal thermostat, without thermostat, and clogged/damaged thermostat. Cooling system temperature and exhaust emissions (CO, HC, and CO₂) were measured at idle speed (800–1000 rpm) for 10 minutes with 2-minute intervals. The data were analyzed using descriptive comparative statistical analysis. The results show that the normal thermostat maintained the most stable operating temperature, reaching 95.8°C at the 8th minute. In contrast, the engine without a thermostat experienced unstable temperature increases and reached 93.4°C at the 10th minute, while the clogged thermostat condition produced the highest temperature of 96.6°C, indicating overheating potential. Removing the thermostat increased CO emissions from 0.01% to 0.04% and HC emissions from 31.7 ppm to 52.3 ppm. These findings confirm that thermostat condition significantly affects engine thermal stability and combustion efficiency; therefore, thermostat removal is not recommended.